Cosmos - Sagan, Carl, 1934-1996. (London : Futura Publications, 1983)
This book is about science in its broadest human context, how science and civilization grew up together. It is the story of our long journey of discovery and the forces and individuals who helped to shape modern science, including Democritus, Hypatia, Kepler, Newton, Huygens, Champollion, Lowell and Humason. The book also explores spacecraft missions of discovery of the nearby planets, the research in the Library of ancient Alexandria, the human brain, Egyptian hieroglyphics, the origin of life, the death of the Sun, the evolution of galaxies and the origins of matter, suns and worlds. The author retraces the fifteen billion years of cosmic evolution that have transformed matter into life and consciousness, enabling the cosmos to wonder about itself. He considers the latest findings on life elsewhere and how we might communicate with the beings of other worlds.
Shores of the cosmic ocean -- One voice in the cosmic fugue -- Harmony of worlds -- Heaven and hell -- Blues for a red planet -- Travelers' tales -- Backbone of night -- Travels in space and time -- Lives of the stars -- Edge of forever -- Persistence of memory -- Encyclopaedia galactica -- Who speaks for Earth?
Include bibliographical references (p. 383-395) and index.
Keywords: Astronomy -- Popular works